Developing Sustainable Technology through Ethical AI Governance Models in Business Environments - Henderi; Aini, Qurotul; Purwanti, Purwanti; Muti, Rifqa Nabila; Fletcher, Eamon (ADI Publisher, 2025)
The rapid adoption of Artificial Intelligence (AI) in business offers transfor- mative opportunities but introduces ethical challenges requiring robust gover- nance models. This study investigates the development of ethical AI gover- nance frameworks to align technology adoption with societal values and sus- tainability goals. Through a mixed-methods approach, qualitative interviews with industry experts and quantitative case study analyses are conducted to ex- plore best practices and key challenges. Findings emphasize the necessity of transparency, stakeholder engagement, and regulatory compliance in fostering trust and accountability within AI-driven processes. The research concludes by proposing a comprehensive governance model that integrates ethical princi- ples with innovation, offering practical solutions for businesses to sustainably leverage AI while mitigating risks and enhancing societal benefits. This study contributes to the growing discourse on sustainable technology and responsible AI deployment in business environments.